Worldwide experience with a totally subcutaneous implantable defibrillator: early results from the EFFORTLESS S-ICD Registry. (26th March 2014) - Lambiase, Pier D.; Barr, Craig; Theuns, Dominic A.M.J.; Knops, Reinoud; Neuzil, Petr; Johansen, Jens Brock; Hood, Margaret; Pedersen, Susanne; Kääb, Stefan; Murgatroyd, Francis; Reeve, Helen L.; Carter, Nathan; et al.
Abstract : Aims: The totally subcutaneous implantable-defibrillator (S-ICD) is a new alternative to the conventional transvenous ICD system to minimize intravascular lead complications. There are limited data describing the long-term performance of the S-ICD. This paper presents the first large international patient population collected as part of the EFFORTLESS S-ICD Registry. Methods and results: The EFFORTLESS S-ICD Registry is a non-randomized, standard of care, multicentre Registry designed to collect long-term, system-related, clinical, and patient reported outcome data from S-ICD implanted patients since June 2009. Follow-up data are systematically collected over 60-month post-implant including Quality of Life. The study population of 472 patients of which 241 (51%) were enrolled prospectively has a mean follow-up duration of 558 days (range 13–1342 days, median 498 days), 72% male, mean age of 49 ± 18 years (range 9–88 years), 42% mean left ventricular ejection fraction. Complication-free rates were 97 and 94%, at 30 and 360 days, respectively. Three hundred and seventeen spontaneous episodes were recorded in 85 patients during the follow-up period. Of these episodes, 169 (53%) received therapy, 93 being for Ventricular Tachycardia/Fibrillation (VT/VF). One patient died of recurrent VF and severe bradycardia. Regarding discrete VT/VF episodes, first shock conversion efficacy was 88% with 100% overall successful clinical conversion after a maximum of five shocks. The 360-day inappropriate shock rate was 7% with the vast majority occurring for oversensing (62/73 episodes), primarily of cardiac signals (94% of oversensed episodes). Conclusion: The first large cohort of real-world data from an International patient S-ICD population demonstrates appropriate system performance with clinical event rates and inappropriate shock rates comparable with those reported for conventional ICDs. Clinical trial registration URL: http://www.clinicaltrials.gov . Unique identifier NCT01085435.